Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3201/eid2408.180309
|View full text |Cite
|
Sign up to set email alerts
|

Probable Locally AcquiredBabesia divergens–Like Infection in Woman, Michigan, USA

Abstract: We report an asplenic patient who was infected with Babesia divergens–like/MO-1. The clinical course was complicated by multiorgan failure that required intubation and dialysis. The patient recovered after an exchange transfusion and antimicrobial drug therapy. Physicians should be alert for additional cases, particularly in asplenic persons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 15 publications
(18 reference statements)
0
15
0
Order By: Relevance
“…Namely, B. duncani (93,94) and a Babesia sp. (95) closely related to B. duncani were identified as causes of infection in Washington and California (WA-1), while B. divergens or B. divergens-like/MO-1 (96, 97) parasites have caused infections in Missouri, Kentucky, Washington, Arkansas, and Michigan (98,99).…”
Section: Epidemiology and Ecologymentioning
confidence: 99%
“…Namely, B. duncani (93,94) and a Babesia sp. (95) closely related to B. duncani were identified as causes of infection in Washington and California (WA-1), while B. divergens or B. divergens-like/MO-1 (96, 97) parasites have caused infections in Missouri, Kentucky, Washington, Arkansas, and Michigan (98,99).…”
Section: Epidemiology and Ecologymentioning
confidence: 99%
“…In addition, Scott et al reported Bbsl in H. leporispalustris collected from songbirds [22]. Reports of human cases with high levels of parasitemia caused by B. divergens-like microorganisms include residents of Missouri, Kentucky, Washington, Arkansas, Massachusetts, and Michigan [90]. In the latter case, Herc et al reported an asplenic Michigan patient infected with a B. divergens-like/MO-1 piroplasm, and this 60-year-old lady experienced fatigue, nausea, and hemolytic febrile symptoms [90].…”
Section: Co-infected Ticks On Terrestrial Mammalsmentioning
confidence: 99%
“…Reports of human cases with high levels of parasitemia caused by B. divergens-like microorganisms include residents of Missouri, Kentucky, Washington, Arkansas, Massachusetts, and Michigan [90]. In the latter case, Herc et al reported an asplenic Michigan patient infected with a B. divergens-like/MO-1 piroplasm, and this 60-year-old lady experienced fatigue, nausea, and hemolytic febrile symptoms [90]. Not only have B. divergens-like infections been identified in the blood and spleen of eastern cottontail rabbits, they have also been detected in rabbit-associated ticks, I. dentatus, on Nantucket Island, Massachusetts, USA [91].…”
Section: Co-infected Ticks On Terrestrial Mammalsmentioning
confidence: 99%
“…B. divergens infects ruminants in Europe but has never been reported in the USA. B. divergens-like/MO-1 in the USA is a distinct strain of B. divergens, which has a lower infection rate in cattle, and distinct morphology when grown in vitro (21,22,23).…”
Section: Discussionmentioning
confidence: 99%